Solutions

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: (a) cosh2 x0 = 1 + sinh2 x0 = 1 + (2)2 = 5, cosh x0 = (b) sinh2 x0 = cosh2 x0 − 1 = 9 25 3 −1= , sinh x0 = (because x0 > 0) 16 16 4 (c) sech2 x0 = 1 − tanh2 x0 = 1 − cosh x0 = √ 5 4 5 2 =1− 9 16 3 = , sech x0 = , 25 25 5 sinh x0 1 5 = , from = tanh x0 we get sinh x0 = sech x0 3 cosh x0 5 3 4 5 = 4 3 Exercise Set 8.8 6. 284 d cosh x d 1 cschx = =− = − coth x csch x for x = 0 dx dx sinh x sinh2 x d 1 sinh x d sech x = =− = − tanh x sech x for all x dx dx cosh x cosh2 x d cosh x sinh2 x − cosh2 x d coth x = = = − csch2 x for x = 0 dx dx sinh x sinh2 x dy dy dx = cosh y ; so dx dy dx 1 1 =√ for all x. 2 1 + x2 1 + sinh y 7. (a) y = sinh−1 x if and only if x = sinh y ; 1 = 1 dy d [sinh−1 x] = = = dx dx cosh y (b) Let x ≥ 1. Then y = cosh−1 x if and only if x = cosh y ; 1 = 1 dy d [cosh−1 x] = = = dx dx sinh y 1 cosh y − 1 2 = x2 dy dy dx = sinh y , so dx dy dx 1 for x ≥ 1. −1 −1 (c) Let −1 < x < 1. Then y = tanh x if and only if x = tanh y ; thus dy 1 dy d dy dy dx = sech2 y = (1 − tanh2 y ) = 1 − x2 , so [tanh−1 x] = = . 1= dx dy dx dx dx dx 1 − x2 9. 4 cosh(4x − 8) 12. 2 15. 1 11. − csch2 (ln x) x 10. 4x3 sinh(x4 ) sech2 2x tanh 2x 13. 1 csch(1/x) coth(1/x) x2 2 + 5 cosh(5x) sinh(5x) 14. −2e2x sech(e2x ) tanh(e2x ) 16. 6 sinh2 (2x) cosh(2x) 2 4x + cosh (5x) √ √ √ 17. x5/2 tanh( x) sech2 ( x) + 3x2 tanh2 ( x) 18. −3 cosh(cos 3x) sin 3x 1 20. 1+ 22. 1/ 1/x2 19. (−1/x2 ) = − 1 √ |x| x2 + 1 √ (sinh−1 x)2 − 1 1 + x2 26. (sech2 x)/ 1 + tanh2 x 27. − 1 sinh7 x + C 7 = 1/ 9 + x2 23. −(tanh−1 x)−2 /(1 − x2 ) 25. 31. 1+ 1 3 x2 /9 √ 21. 1/ (cosh−1 x) x2 − 1 24. 2(coth−1 x)/(1 − x2 ) 28. 10(1 + x csch−1 x)9 − 1 sinh x cosh x − 1 2 = sinh x = | sinh x| 1, x > 0 −1, x < 0 ex √ + ex sech−1 x 2x 1 − x x √ + csch−1 x |x| 1 + x2 32. 1 sinh(2x − 3) + C 2 33. 2 (tanh x)3/2 + C 3 285 Chapter 8 1 34. − coth(3x) + C 3 37. ln 3 1 − sech3 x 3 39. u = 3x, 40. x = √ ln 3 = 37/375 38. ln(cosh x) 0 ln 2 1 3 √ √ 2u, = ln 5 − ln 3 1 1 du = sinh−1 3x + C 2 3 1+u √ 2 du = −2 √ 2u2 1 u2 −1 √ du = cosh−1 (x/ 2) + C 1 du = − sech−1 (ex ) + C u 1 − u2 √ 41. u = ex , √ 42. u = cos θ, − 1 du = − sinh−1 (cos θ) + C 1 + u2 du = − csch−1 |u| + C = − csch−1 |2x| + C u 1 + u2 √ 43. u = 2x, √ 44. x = 5u/3, 1/2 45. tanh−1 x 0 46. sinh−1 t 1 36. − coth3 x + C 3 35. ln(cosh x) + C √ 3 1 5/3 du = 2 − 25 3 25u 1 u2 −1 = tanh−1 (1/2) − tanh−1 (0) = = sinh−1 √ 0 ln 3 sinh 2x dx = 49. A = √ 0 du = 1 cosh−1 (3x/5) + C 3 1 1 1 + 1/2 ln = ln 3 2 1 − 1/2 2 √ 3 − sinh−1 0 = ln( 3 + 2) ln 3 1 cosh 2x 2 = 0 1 [cosh(2 ln 3) − 1], 2 1 1 1 but cosh(2 ln 3) = cosh(ln 9) = (eln 9 + e− ln 9 ) = (9 + 1/9) = 41/9 so A = [41/9 − 1] = 16/9. 2 2 2 ln 2 ln 2 sech2 x dx = π tanh x 50. V = π 0 = π tanh(ln 2) = 3π/5 0 5 5 (cosh2 2x − sinh2 2x)dx = π 51. V = π 0 1 cosh ax dx = 2, 52. 0 dx = 5π 0 1 sinh ax a 1 = 2, 0 1 sinh a = 2, sinh a = 2a; a let f (a) = sinh a − 2a, then an+1 = an − sinh an − 2an , a1 = 2.2, . . . , a4 = a5 = 2.177318985. cosh an − 2 53. y = sinh x, 1 + (y )2 = 1 + sinh2 x = cosh2 x ln 2 ln 2 cosh x dx = sinh x L= 0 = sinh(ln 2) = 0 1 ln 2 1 (e − e− ln 2 ) = 2 2 2− 1 2 = 3 4 Exercise Set 8.8 286 54. y = sinh(x/a), 1 + (y )2 = 1 + sinh2 (x/a) = cosh2 (x/a) x1 x1 L= cosh(x/a)dx = a sinh(x/a) 0 = a sinh(x1 /a) 0 55. sinh(−x) = cosh(−x) = 1 1 −x (e − ex ) = − (ex − e−x ) = − sinh x 2 2 1 1 −x (e + ex ) = (ex + e−x ) = cosh x 2 2 1 1x (e + e−x ) + (ex − e−x ) = ex 2 2 1x 1x (b) cosh x − sinh x = (e + e−x ) − (e − e−x ) = e−x 2 2 1x 1 (c) sinh x cosh y + cosh x sinh y = (e − e−x )(ey + e−y ) + (ex + e−x )(ey − e−y ) 4 4 56. (a) cosh x + sinh x = = 1 x+y [(e − e−x+y + ex−y − e−x−y ) + (ex+y + e−x+y − ex−y − e−x−y )] 4 1 (x+y) [e − e−(x+y) ] = sinh(x + y ) 2 Let y = x in part (c). The proof is similar to part (c), or: treat x as variable and y as constant, and differentiate the result in part (c) with respect to x. Let y = x in part (e). Use cosh2 x = 1 + sinh2 x together with part (f). Use sinh2 x = cosh2 x − 1 together with part (f). = (d) (e) (f ) (g) (h) 57. (a) Divide cosh2 x − sinh2 x = 1 by cosh2 x. sinh y sinh x + tanh x + tanh y sinh x cosh y + cosh x sinh y cosh x cosh y = = (b) tanh(x + y ) = sinh x sinh y cosh x cosh y + sinh x sinh y 1 + tanh x tanh y 1+ cosh x cosh y (c) Let y = x in part (b). 1 58. (a) Let y = cosh−1 x; then x = cosh y = (ey + e−y ), ey − 2x + e−y = 0, e2y − 2xey + 1 = 0, 2 √ 2x ± 4x2 − 4 y = x ± x2 − 1. To determine which sign to take, note that y ≥ 0 e= 2 √ so e−y ≤ ey , x = (ey + e−y )/2 ≤ (ey + ey )/2 = ey , hence ey ≥ x thus ey = x + x2 − 1, √ y = cosh−1 x = ln(x + x2 − 1). ey − e−y e2y − 1 , xe2y + x = e2y − 1, = 2y ey + e−y e +1 1 1+x 1+x , y = ln . = (1 + x)/(1 − x), 2y = ln 1−x 2 1−x (b) Let y = tanh−1 x;...
View Full Document

This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online